Posterior Distraction Using Springs in Syndromic and Multisuture Craniosynostosis: Improving the Technique. Issue 7 (October 2020) - Mathijssen, Irene M.J.; Driessen, Caroline; Versnel, Sarah L.; Dremmen, Marjolein H.G.; van Veelen, Marie-Lise C.
Abstract : Introduction: Posterior distraction is the preferred surgical treatment for particularly Apert and Crouzon syndrome in most craniofacial centers, using either external distractors or springs. The authors prefer the use of springs and have adapted their technique to further improve outcomes. Methods: All patients who were treated with the adapted technique for occipital expansion using springs were included. The most significant adaption that the authors introduced in 2017 is using a bony hinge at the top of the vault instead of at the caudal edge of the occiput. Results: A total of 8 posterior expansions with springs were performed. No complications occurred and the springs were also successfully applied in cases with extremely thin bone. If indicated, a simultaneous foramen magnum decompression was performed and this was easier to combine with a hinge at the top of the vault. Conclusions: Posterior distraction with springs is a safe and effective procedure and allows a simultaneous foramen magnum decompression. Planning the hinge at the vault allows intracranial volume gain at the site of the posterior skull base. Abstract : Supplemental Digital Content is available in the text